2010
DOI: 10.1007/s12088-010-0056-3
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial endophytic fungal assemblages inhabiting bark of Taxus baccata L. of Indo-Burma mega biodiversity hotspot

Abstract: Fungal endophytes were isolated from inner bark of Taxus baccata L., an important source of potent anticancer drug taxol. Bark samples were collected from two locations of Arunachal Pradesh, India, part of the IndoBurma mega biodiversity hotspot, during two seasons i.e. monsoon and winter. Altogether 77 fungal strains representing 18 genera were isolated from T. baccata bark during the present investigation. The colonizing frequency was recorded as 38.5% and the fungal community comprised of 78% of Hyphomycete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…However, none of the previous studies report it as an endophyte associated with the Taxus plant species. Consistent with earlier reports from Taxus chinensis (Zhou et al 2009;Tayung & Jha 2010), we also identified the NFW6 isolate as a strain of Mucor hiemalis. NFW8 was identified as Chaetomium which resides within various plants such as Curcuma wenyujin, Viguiera robusta and Taxus globosa (Momesso et al 2008;Wang et al 2010;Soca-Chafre et al 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, none of the previous studies report it as an endophyte associated with the Taxus plant species. Consistent with earlier reports from Taxus chinensis (Zhou et al 2009;Tayung & Jha 2010), we also identified the NFW6 isolate as a strain of Mucor hiemalis. NFW8 was identified as Chaetomium which resides within various plants such as Curcuma wenyujin, Viguiera robusta and Taxus globosa (Momesso et al 2008;Wang et al 2010;Soca-Chafre et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…It is well established that endophytes are capable of producing remarkable cancer chemotherapeutic agents (Tayung & Jha 2010;Cragg & Pezzuto 2015). This investigation of biological activities mediated by endophytic fungi isolated from Taxus fuana indicates their diverse potential for the generation of bioactive metabolites.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, it was reported that crude extracts obtained with ethyl acetate from a fermented broth of Fusarium sp. isolated from T. baccata showed significant antimicrobial activity against all pathogens tested (i.e., Bacillus subtilis, Staphylococcus epidermis, Staphylococcus aureus, Klebsiella pneumoniae, Shigella flexneri, Escherichia coli, Candida albicans , and Candida tropicalis ) [33]. Similarly, among the 16 endophytic fungi isolated during our study, Annulohypoxylon sp.…”
Section: Discussionmentioning
confidence: 51%
“…For example, a Taxol‐producing endophyte induces transcription of genes encoding a redundant fungicide pathway in its host Taxus , and prevents colonization of its fungal competitors at minimal metabolic cost. Fifteen fungal isolates from T. baccata displayed antimicrobial activity . Perenniporia tephropora , an endophytic fungus of T. mairei , had strong anti‐ Pyricularia oryzae activity and produced the cytotoxic metabolites .…”
Section: Introductionmentioning
confidence: 99%